Identification of Leases Under the New Leasing Standard - Poon , Wing W. (Journal of Accounting and Finance, 2021)
The Financial Accounting Standards Board issued significantly revised standard on lease accounting in 2016. The new standard became effective for annual reporting periods beginning after December 15, 2018, including interim reporting periods within those reporting periods for public business entities. Under the new standard, a lessee recognizes a right-of-use asset and a lease liability for all leases, including operating leases with a term greater than 12 months, which will significantly increase the reported assets and liabilities for many lessees. The critical accounting determination is whether or not a contract is/contains a lease. This determination becomes the new on- or off-balance sheet test. This paper discusses the concepts of identified assets and of the right to control the use of an asset. Examples are used to illustrate the application of the concepts.